The Legitimacy of the Deed of Power of Attorney Imposing Mortgage Right Signed Before the Date of the Deed Issuance in the Conception of Legal Certainty - Akirin, Akirin (Jurnal Konstatering, 2022)
The mechanism for signing a notarial deed is not only limited to the issue that the deed must be signed, but the signing of the deed must also be before a notary as stipulated in Article 16 paragraph (1) UUJN. The purpose of this study is to analyze the provisions for imposing mortgage rights under the current law, the factors behind the signing of the Deed of Power of Attorney for imposing mortgage rights before the date the deed is issued or in other words the deed is signed without being given the date and number of the deed, and legal consequences of signing the Deed of Power of Attorney to incur Mortgage before the date the deed is issued, in other words the deed is signed without being given the date and number of the deed. The research approach method used in this thesis is a sociological juridical legal research method. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Constitution; Act No. 2 of 2014; Mortgage Act; Code of Civil law; as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The results of the study show that the provisions regarding the deed of Power of Attorney Imposing Mortgage made by a Notary are fully regulated by law, so the signing of the Deed of Power of Attorney Imposing Mortgage made by a notary without being given a date and number has legal consequences that the deed made by the notary only has the force of law as a deed under the hand because it is not in accordance with the provisions of Article 16 paragraph (1) of Act No. 2 of 2014 amendment to Act No. 30 of 2004 Concerning the Office of a Notary.Keywords: Attorney; Power; Signature.